From Combustion to Conversion: Impact of Heating Demand Decrease on District Heating Systems - Vassallo, Ona; Kontu, Kaisa (International Journal of Sustainable Energy Planning and Management, 2026)
Climate change is expected to reduce heating demand in Finnish buildings, impacting district heating (DH) systems. This study models small, medium, and large DH systems for the years 2030 and 2050 using Representative Concentration Pathway (RCP) climate scenarios. The analysis uses energyPRO to simulate system operations based on fuel price prioritization, comparing future scenarios to a 2023 baseline. The transition from high-emission systems to sustainable energy sources—such as waste heat, electric boilers, and nuclear—poses challenges for revenue and energy security. While national-level studies exist, local-level insights are limited. Results show that reduced heat demand can lead to significant revenue losses in current systems, although renewable heat production increases. Smart future systems that minimize fossil fuel combustion and rely on biomass-based renewables maintain more stable revenues due to lower emission costs and consistent fuel pricing. These findings support strategic planning for sustainable, cost-effective DH systems aligned with national and EU climate goals.